Utrata wartości przez wartość firmy - Ziętowska, Irena (Impairment of the Value of Goodwill, 2005)
The balance sheet law provides quite an overall view of the impairment of the value of assets. It fails to consider a number of particular aspects that pertain to a specific item of fixed assets, i.e., goodwill which belongs to the intangible and legal assets of a company. IAS 36 The Impairment of the Value of Assets' includes a thorough and broad approach to the impairment of the value of assets and procedures that are related to its appraisal. The paper analyses selected aspects of the impairment of value of goodwill regarded as one of many asset items of a business in line with the International Accounting Standards set against the provisions set forth in the Accounting Act.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 367-380